On the Work of the General Agreement on Trade and Tariffs (GATT) (Czech Journal of International Relations, 1966)
GATT is the oldest post-war institution charged with regulating some multilateral norms of international trade. Czechoslovakia is interested in this organization because of the high degree of its participation in international division of labour. The per capita share of foreign trade turnover in Czechoslovakia exceeded already in 1963 the world average three times. Basically, GATT is a multilateral general trade agreement by which the contracting parties mutually obligate themselves to observe agreed rules in their trade relations; in particular, that they grant each other the most favored nation clause in tariffs and other regulations pertaining to imports and exports. Within the framework of GATT, several custom tariff conferences were held since 1947.